Analysis of Knowledge Sharing Determinants and Their Impact on Sustainability Organization Performance in Private Universities - Lisnatiawati Saragih; Djamarel Hermanto (Universitas Mercu Buana, 2022)
Objectives: The main objective of business is the achievement of sustainable organizational performance, including higher education. But in the process, many obstacles are faced by an organization. Sharing knowledge is a way to help employees in solving problems faced in the world of work. This study examines the mediating role of knowledge sharing to mediate the influence between academic culture and professional competence on sustainable organizational performance.Methodology: The data in this study were obtained by distributing questionnaires to 380 respondents, the data in this study was analyzed using the SEM-PLS approach to explore the consistency of the findings on the correlation between variables.Finding: The findings show that knowledge sharing is able to mediate the influence of the variables of academic culture and professional competence on sustainable organizational performanceConclusion: The results obtained are that knowledge sharing has a positive and significant effect on organizational sustainability performance, knowledge sharing is found to fully mediate the relationship between academic culture and organizational sustainability performance, and knowledge sharing is found to partially mediate the relationship between professional competence and organizational sustainability performance.